2008
DOI: 10.1111/j.1475-097x.2008.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Obese children show increased intimal wall thickness and decreased pulse wave velocity

Abstract: Obese children and adolescents, primarily females, present with increased RA IT. The decreased PWV in the obese versus lean subjects might reflect general vasodilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
85
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 43 publications
11
85
1
6
Order By: Relevance
“…The negative association between obesity and vascular stiffness observed in children 16 and adolescents 14,15 and the positive association reported in older adults and the elderly [7][8][9]12 are consistent with our findings across the adult age span and support the hypothesis that during adulthood, the physiological relationship between obesity and vascular function alters. We also observed that both high body fat and reduced lean mass were associated with lower PWV in younger adults.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The negative association between obesity and vascular stiffness observed in children 16 and adolescents 14,15 and the positive association reported in older adults and the elderly [7][8][9]12 are consistent with our findings across the adult age span and support the hypothesis that during adulthood, the physiological relationship between obesity and vascular function alters. We also observed that both high body fat and reduced lean mass were associated with lower PWV in younger adults.…”
Section: Discussionsupporting
confidence: 81%
“…In older adults, there are data that indicate increasing arterial stiffness with obesity, [7][8][9] although findings have been inconsistent across studies. [10][11][12][13] In contrast, obese children have reduced arterial stiffness compared with their normal weight peers, [14][15][16] an effect thought to result from physiological adaptation to the hyperemic state of obesity in the young. 16 Taken together these contrasting data from young and old populations suggest age-related differences in the relationship between body composition and arterial stiffness, which have not been fully explored.…”
mentioning
confidence: 99%
“…In adults, a positive relationship between obesity and PWV has been described in cross-sectional studies, 22,23 and a reduction in PWV was observed after losing weight, 24 although these studies had not considered the impact of BP values at the same time. Controversial results exist in the childhood population 14,25,26 that may be partially explained by differences in patient populations (age, sex, and small sample size) and heterogeneity of the techniques used. In our study, the vascular phenotype assessment was performed in a large number of nonobese and obese subjects by the same operators with homogeneous methodology in only 1 center.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations are manifested not only in high peripheral or central BP 11 but also in reflecting waves 12,13 and in pulse wave velocity (PWV). 14 These intermediate phenotypes, as an expression of functional or structural abnormalities in the vascular tree, can be the cause, as well as the consequence, of early vascular alterations. Vascular phenotypes of large vessels provide a novel viewpoint for studying functional abnormalities, and because it can be clinically relevant, it represents a field of growing interest.…”
mentioning
confidence: 99%
“…The intra-individual variation (the coefficient of variation of repeated measurements by the same operator) was 8.1% for the IT and 4.0% for IMT of the radial artery and 1.5% for the diameter of the radial artery. 14 …”
Section: Ultrasound Measurementsmentioning
confidence: 99%